THE ART OF MAKING WAU BULAN : SHAFIE JUSOH - Hamidah Abdul Rahman author 358679; Mohd. Firdaus Mohd. Herrow author photographer designer 631864; Nizar Nazrin author editor 631865; Farah Merican Isahak Merican author editor 631866; Hamidah Abdul Rahman photographer designer 358679 (Kota Bharu, Kelantan : Penerbit Universiti Malaysia Kelantan, 2014)
A great effort has been put this book in orger to preserve one of Malaysia's precious hentages, the Wau Bulan For approximately 100 days or filed work and interviews with Malaysia Craft Master En Shafie Jusoh we have finally completed this book. Days were spent with him to understand each stage in wau making. We believe the processes behind the existence of a Wau Bulan are worth the preservation As a great man once said Let save what remains not by vaults and ocks which fence them from the public eye and use in consigning them to the waste of time but by such a multiplication of copies, an shat place them beyond the reach of accident, we believe that the book will serve as a refence to all in search of Malaysia craft making. Imation was successfully gathered despite language dialect barmer Notes were compiled.compared checked and efforts were devoted producing a book that highlights the beauty of Wau Bulan and how to make such intricate art. Priotos featured in this book are taken using the creative igrang system, This is to ensue that the quality of photos will give justice to the beauty in each creation of the Wau Bulan. A wau is not an ordinary kite that is put in air just for fun : it is an art that focuses on aesthetic design and cultural content of the Malays. Looking at frequent used motifs like "awan larat", this motif symbolize a slow and smooth hand dancing as well as comunity of a human's life. Shafie Jusoh, International renown Wau maker shared his experiences and knowledge of Wau making. This bok were compiled, compared, checked and efforts were devoted in producing a book that highlights the beauty of Wau Bulan and how to make such intricate art. Photos featured in this book are taken using the creative lighting system. This is to ensure that the quality of photos will give justice to the beauty in each creative of the Wau Bulan.